Urgent natural foci infections transmitted by ticks in Saint-Petersburg - V. V. Nechaev; A. A. Yakovlev; A. N. Uskov; L. E. Boburina; N. V. Lavrova; M. N. Pogromskaya; B. I. Aslanov; A. O. Shapar; S. V. Pavlenko; L. N. Pozhidaeva; A. K. Ivanov; A. I. Kravtsova; et al. (Журнал инфектологии, 2018)
Purpose: to conduct a comparative analysis and to identify the epidemiological and clinical features of tick-borne encephalitis (TBE) and Lyme borreliosis as a mono- and coinfections in St. Petersburg. Materials and methods. 718 cases of TBE, 4353 cases of Lyme borreliosis and 127 combined diseases registered by the St. Petersburg epidemiological bureau in 2006-2017 were studied. Identification of combined diseases was carried out by a special software that allows to identify co-morbid diseases from the array of monoinfections. To identify clinical and epidemiological features, 144 cases of TBE, 286 Lyme borreliosis, and 43 cases of co-infection were studied. Age and sex characteristics, places of human contagion, infection rates of ticks, clinical forms of mono- and associated diseases, morbidity dynamics changes and patients’ IgM seropositivity were studied. Results. The long-term dynamics of TBE and Lyme borreliosis incidence had did not have significant upward or downward trends, it was characterized by synchronous fluctuations. The priority of the incidence of men over women is revealed. 61–69% cases of TBE and Lyme borreliosis occurred in Leningrad region, 19–30% – in the adjacent territories of Russia, 5,7–6,7% of cases were imported from other countries. High tick infection rates of TBE virus and Borrelia was revealed. Borrelia аnd virus of TBE and were detected in 81,6–87,5% of the examined ticks removed from patients with a later established diagnosis. Seasonal distribution of Lyme borreliosis was shifted by a month to the right in comparison with TBE. The clinical forms of both diseases did not differ in their structure from the country data, however after 2012 subclinical forms were more common in women. The proportion of non-erythematous forms of Lyme borreliosis in 2011–2015 compared with the 2006–2010 observation period increased almost 1,5-fold mainly forms, including those with co-infection. The IgM seropositivity rate in the dynamics of the disease testifies to the incomplete rehabilitation of patients. Conclusion. The clinical and epidemiological characteristics of TBE, Lyme borreliosis and combined infection in the North-West region of Russia, with the example of St. Petersburg, have certain distinctive features. The reasons for the revealed features need further study.